(3CfhGQ GdabGgIs - (3GdfLaj, cGTa GdZWGA, MSf Hf LYaQ Hf NVQ GdLfGMj, J (B1262(3g` (B1846(3es
(3ChdgG (B:s
(3ChdgG(B: (3efg ddTc aj KHhJ GdbUGU Ydjg HQO jejf GdSjO Ydi eOYjg hCeQ GdOeGA YXje, fYe jKHJ GdeGd aj QbHI GdSjO dCf GdYHO eGd aEPG QO Gdjejf Ydi GdeOYj ajs
(3BNQgG (B:s
(3BNQgG(B: (3fYe bO jKHJ GdeGd aj PeJg HYO GdYJb dG Mjf chfg eedhcG hcPG dh GOYi CMO Ydi GdSjO bUGUG Ydi GdYHO aQO GdSjO Gdjejf Ydi GdeOYi aEf GdYHO dG jbJU efgs
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B1: 543s
(3GdPQjYI, L (B2: 244s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis